Pathways to Care for Critically Ill or Injured Children: A Cohort Study from First Presentation to Healthcare Services through to Admission to Intensive Care or Death. - Peter Hodkinson; Andrew Argent; Lee Wallis; Steve Reid; Rafael Perera; Sian Harrison; Matthew Thompson; Mike English; Ian Maconochie; Alison Ward (PLoS ONE)
Purpose Critically ill or injured children require prompt identification, rapid referral and quality emergency management. We undertook a study to evaluate the care pathway of critically ill or injured children to identify preventable failures in the care provided. Methods A year-long cohort study of critically ill and injured children was performed in Cape Town, South Africa, from first presentation to healthcare services until paediatric intensive care unit (PICU) admission or emergency department death, using expert panel review of medical records and caregiver interview. Main outcomes were expert assessment of overall quality of care; avoidability of severity of illness and PICU admission or death and the identification of modifiable factors. Results The study enrolled 282 children, 252 emergency PICU admissions, and 30 deaths. Global quality of care was graded good in 10% of cases, with half having at least one major impact modifiable factor. Key modifiable factors related to access to care and identification of the critically ill, assessment of severity, inadequate resuscitation, and delays in decision making and referral. Children were transferred with median time from first presentation to PICU admission of 12.3 hours. There was potentially avoidable severity of illness in 185 (74%) of children, and death prior to PICU admission was avoidable in 17/30 (56.7%) of children. Conclusions The study presents a novel methodology, examining quality of care across an entire system, and highlighting the complexity of the pathway and the modifiable events amenable to interventions, that could reduce mortality and morbidity, and optimize utilization of scarce critical care resources; as well as demonstrating the importance of continuity and quality of care.